Reformationsjubilæernes iscenesættelse af samhørighed mellem stat, kirke og folk i Danmark - Warburg, Margit (Religionsvidenskabeligt Tidsskrift, 2018)
ENGLISH ABSTRACT: The 500th anniversary of the onset of the Lutheran reformation was celebrated in Denmark during most of 2017. Unlike the celebrations in Norway, Sweden and Germany, the Danish celebrations had a remarkable focus on the national significance of the Reformation. The celebrations ranged from large, state-sponsored national events to more than one thousand local arrangements involving civil society, educational institutions and parishes. This article analyses some of the historical Reformation jubilees in Denmark and compare them to fresh empirical material from the Danish Reformation jubilee in 2017. The analysis shows, among other things, that a recurrent theme in the celebrations was a claim of a special relationship between Denmark and God, which is a clear expression of Danish civil religion. Examples of civil-religious statements and activities are presented. DANSK RESUMÉ:500-års jubilæet for Reformationens begyndelse blev fejret i Danmark gennem det meste af 2017. I modsætning til fejringerne i Norge, Sverige og Tyskland var de danske fejringer i bemærkelsesværdig grad rettet mod reformationens nationale betydning. Fejringerne rakte fra store, statslige, nationale begivenheder til over et tusinde lokale arrangementer med deltagelse af civilsamfund, uddannelsesinstitutioner og kirkesogne. Denne artikel analyserer nogle af de historiske reformationsjubilæer og sammenligner dem med nyt empirisk materiale fra det danske reformationsjubilæum i 2017. Analysen påviser blandt andet, at et gennemgående tema i fejringerne var en påstand om et særligt forhold mellem Danmark og Gud, hvad der klart er udtryk for dansk civilreligion. I artiklen bliver der givet eksempler på civilreligiøse udsagn og aktiviteter.